Protostylid: A case series - S. V. S. G. Nirmala; Kumar Raja Gaddam; P Vimaladevi; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2013)
Human jaws and teeth display a high degree of morphological individuality as they represent personal, family and population characteristics. A protostylid is a supernumerary or accessory cusp located on the mesial half of the buccal surface on the molars that may seldom pose problems while its presence may not be a cause for alarm in most instances. This case report presents a rare finding of protostylid on the buccal surface of the primary molars in 4 children. From the perspective of forensic dentistry, this morphological feature, though uncommon, may be useful for classification and identification of victims in mass causalities and bite marks on bodies or inanimate objects.